Preparation of ATO-incorporated composite latex with tailored structure and controllable size for highly spectrum-selective applications. (15th October 2019) - Gong, Sheng; He, Tianhao; Zhu, Dandan; Sundaramurthy, Anandhakumar; Li, Qiaoguang; Shu, Xugang
Abstract: We report a low-cost approach for fabricating highly transparent and infrared-shielding coatings by miniemulsion polymerization (MEP). Synthesis of ATO-incorporated composite latex with tailored structure was performed in a controlled manner by optimizing the process conditions via modified MEP. Antimony doped tin oxide (ATO) nanoparticles (NPs) were functionalized with 3-methacryloxy propyl trimethoxysilane (MPS) to improve the crosslinking between ATO NPs and polymers via MEP. ATO-incorporated composite MANs/poly(methyl methacrylate- co -butyl acrylate) (MANs/poly(MMA- co -BA)) latex was obtained by polymerizing ATO-incorporated composite latex with methyl methacrylate (MMA) and butyl acrylate (BA). Investigations revealed homogeneous distribution of ATO NPs in the composite (MANs/poly(MMA- co -BA)) latex owing to the better cross-linking with poly(MMA- co -BA). The spectral selectivity of the MANs/poly(MMA- co -BA) composite film was determined by ultraviolet-visible-near infrared (UV–Vis-NIR) spectroscopy. Interestingly, MANs/poly(MMA- co -BA) films exhibited stronger NIR-shielding properties by blocking up to 70% of NIR radiation in the range of 780–2500 nm while maintaining better visible light transparency of >80%. The results demonstrated that the prepared MANs/poly(MMA- co -BA) latex can be used as a spectrum-selective coating for next-generation transparent and IR-shielding materials. Graphical abstract: Unlabelled Image Highlights: The functionalization of ATO NPs leads to the formation of crosslinking between polymers and NPs. Latex particles with homogeneously incorporated MANs are formed in a controlled manner. MANs/PMB film blocks >70% of NIR light while maintaining >80% of transmittance for the visible light.